Effects of Rhizophagus irregularis on Photosynthesis and Antioxidative Enzymatic System in Robinia pseudoacacia L. under Drought Stress - He, Fei; Sheng, Min; Tang, Ming (Frontiers in Plant Science, 2017)
Black locust (Robinia pseudoacacia L.) is an important legume tree species that is widely used for revegetation in the arid and semi-arid areas of China, where it frequently encounters drought stress. This study investigated how the presence of AM fungi affected the photosynthesis and antioxidant gene-enzymes response of black locust seedlings to drought stress. Here, pot experiments were performed to investigate the effects of Rhizophagus irregularis (synonym for Glomus intraradices), an AM fungus, on the tissue water content, photosynthesis, reactive oxygen species (ROS) production, antioxidant enzyme activity and gene expression in black locust (Robinia pseudoacacia L.) seedlings which were subjected to well watered or moderate drought stress. Mycorrhizal symbiosis increased relative water content of plant roots and leaves, promoted the accumulation of biomass and chlorophyll (Chl) content, and improved photochemistry efficiency, regardless of watering regimes. Mycorrhizal plants had higher SOD, POD, CAT, APX, and GR activities, and the transcript levels of Cu/Zn-SOD, APX and GR, but lower O2, H2O2 and MDA concentrations in leaves and roots of black locust under drought and well watered conditions. Results from the present study indicate that AM fungus (R. irregularis) symbiosis can enhance photosynthesis and ROS scavenging capabilities and increase relative water content of leaves and roots to alleviate drought stress in black locust. Further research is needed to elucidate the relations among AM fungi and the metabolic pathways of antioxidant enzymes, and the function of antioxidant genes regulated by mycorrhizal symbiosis with the purpose of revealing the mechanisms of mycorrhiza-induced plant tolerance to drought stress.